THE EFFECT OF BETULIN NANOSUSPENSION ON THE QUALITY AND DURATION OF WHEAT BREAD STORAGE - N. V. Zavorohina; N. A. Pankratieva; A. V. Buhler (Современная наука и инновации)
Improving the quality of products, extending the period of preservation of its freshness - the main tasks of bakeries, which is especially important in a competitive struggle for the market.